Pudendal Nerve Block Versus Penile Nerve Block in Children Undergoing Circumcision - Tutuncu, Ayse Cigdem; Kendigelen, Pinar; Ashyyeralyeva, Gulruh; Altintas, Fatis; Emre, Senol; Ozcan, Rahsan; Kaya, Guner (Urology Journal, 2018)
Purpose: Penile nerve block is the most popular nerve block for the circumcision in pediatric patients. This study aimed to compare the analgesic efficiency of penile nerve block and the pudendal nerve block on postoperative pain and additional analgesic requirements in children undergoing circumcision. Material and Methods: This prospective randomized double-blind study enrolled 85 children, aged 1 to10 years, undergoing circumcision. The patients were randomly divided into two groups either receiving dorsal penile block group (PNB-Group) or pudendal nerve block (PDB-Group). In the PNB-Group, 0.3 ml/kg 0.25 % bupivacaine was used; and, in the PDB-Group, 0.3 ml/kg bupivacaine was applied with nerve stimulator at a concentration of 0.25%. In the postoperative period, the modified CHEOPS pain scale scoring and additional analgesic demand were evaluated at the 5th and 30th minutes and at the 1st and 2nd hours. The subsequent pain evaluations were made by the parents at home, at the postoperative 6th, 12th, 18th and 24th hours. Results: Seven patients were excluded from the study, and seventy eight patients were evaluated for analysis. Patients in PDB-Group had significantly lower postoperative pain intensity and lower mCHEOPS scores (3.83 ± 0.98) when compared to the PNB-Group (6.47 ± 0.91) (P < .01) at all measurement times and none of patients in PDB-Group had additional analgesic requirements up to 24 hours. Patients in the PNB-Group had significantly more analgesic requirements at all measurements times except at the 1st, 2nd, 24th hours. 3.8%, 30.8%, 46.2% and 59% of the patients in the PNB group needed additional analgesia respectively at 5th, 6th, 12th and 18th hours. Conclusion: Pudendal nerve block provided additional analgesic free period and had better analgesic efficiency compared to the penile nerve block lasting until 24 hours after operation.